2020
DOI: 10.1103/physrevd.102.056023
|View full text |Cite
|
Sign up to set email alerts
|

New physics in B meson mixing: Future sensitivity and limitations

Abstract: The mixing of neutral mesons is sensitive to some of the highest scales probed in laboratory experiments. In light of the planned LHCb Upgrade II, a possible upgrade of Belle II, and the broad interest in flavor physics in the tera-Z phase of the proposed FCC-ee program, we study constraints on new physics contributions to B d and B s mixings which can be obtained in these benchmark scenarios. We explore the limitations of this program, and identify the measurement of jV cb j as one of the key ingredients in w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…The scale of dimension-6 operators contributing to neutral meson mixing is typically constrained to be higher by the data than the scales of operators affecting decays. A recent analysis of future sensitivities observed that beyond the Belle II and LHCb data taking in this decade, future improvements are hindered by the expected uncertainty of |V cb | [12]. To go beyond current expectations and reach the per mille level, not yet known theoretical progress would be needed.…”
Section: P Violation and Bsm Physics In B Ds Meson Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale of dimension-6 operators contributing to neutral meson mixing is typically constrained to be higher by the data than the scales of operators affecting decays. A recent analysis of future sensitivities observed that beyond the Belle II and LHCb data taking in this decade, future improvements are hindered by the expected uncertainty of |V cb | [12]. To go beyond current expectations and reach the per mille level, not yet known theoretical progress would be needed.…”
Section: P Violation and Bsm Physics In B Ds Meson Mixingmentioning
confidence: 99%
“…(The theory uncertainties are subject to some recent discussions [10].) At the FCC-ee, the achievable experimental uncertainty has been estimated to be about 2.5 × 10 −5 for both quantities [11,12], which would allow a measurement of A d SL even at the SM level. These measurements would help probe BSM physics, as well as help discriminate between models, should BSM physics be discovered in other processes.…”
Section: P Violation and Bsm Physics In B Ds Meson Mixingmentioning
confidence: 99%
“…( 2) based on their contributions to different meson-mixing observables. We exploit the bounds provided in [13,14] on generic NP contributions. Despite being an effect coming from a dim.-8 operator and being generated at one-loop, given the previous enhancements and the precision with which many of these observables are known, one reaches a sensitivity to multi-TeV NP effects, as shown in Tab.…”
Section: Examplementioning
confidence: 99%
“…In making this argument, it is useful to recall the results of a model-independent study of possible BSM contributions to the B 0 − B 0 and B 0 s − B 0 s mixing amplitudes, reported in Ref. [10]. The box diagrams that drive the oscillations and carry CP-violating phases are natural entry points for any heavy degrees of freedoms from BSM physics.…”
Section: Many Of the Observables In Cp-violation Studies And Others Contributing To Unitaritymentioning
confidence: 99%